2013
DOI: 10.1038/jcbfm.2013.215
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Neural Stem Cells That Overexpress Sod1 Enhances Amelioration of Intracerebral Hemorrhage in Mice

Abstract: Previous studies have shown that intraparenchymal transplantation of neural stem cells (NSCs) ameliorates neurologic deficits in animals with intracerebral hemorrhage (ICH). However, massive grafted cell death after transplantation, possibly caused by a hostile host brain environment, lessens the effectiveness of this approach. We focused on the effect of oxidative stress against grafted NSCs and hypothesized that conferring antioxidant properties to transplanted NSCs may overcome their death and enhance neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 42 publications
0
33
0
Order By: Relevance
“…The efficacy of free radical scavengers has provided direct evidence for a causal relationship between ROS and ICH injury. Specifically, overexpression of copper/zinc-superoxide dismutase (Wakai, et al, 2014) or treatment with deferoxamine (Cui, et al, 2015, Ni, et al, 2015, H. Wu, et al, 2011), a chelator of pro-oxidative iron, significantly reduced brain injury in animal models of ICH.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of free radical scavengers has provided direct evidence for a causal relationship between ROS and ICH injury. Specifically, overexpression of copper/zinc-superoxide dismutase (Wakai, et al, 2014) or treatment with deferoxamine (Cui, et al, 2015, Ni, et al, 2015, H. Wu, et al, 2011), a chelator of pro-oxidative iron, significantly reduced brain injury in animal models of ICH.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have used neural stem cell transplantation to treat SBI following cerebral hemorrhage, but the host reaction after transplantation led to graft failure and death, which may be related to elevated levels of oxidative stress after transplant. Therefore, Wakai and colleagues transplanted neural stem cells overexpressing SOD1 (copper/zinc-superoxide dismutase) to treat cerebral hemorrhage, which significantly reduced mortality and oxidative stress, speeding up recovery from neurological disorders after ICH [ 196 ].…”
Section: Antioxidant Therapy After Ichmentioning
confidence: 99%
“…SOD1 overexpression in transgenic rats was linked to reduced OS, BBB disruption, and neuronal apoptosis in a Hb-injection model [ 42 ]. A recent study on cell replacement therapy in ICH found that neural stem cells (NSCs) overexpressing SOD1 3 days after ICH could increase neuronal survival, indicating that SOD1 enhancement alone or combined with other treatments may be effective in ICH [ 91 ]. Moreover, SOD1 hyperexpression is also protective against the spontaneous occurrence of ICH in hypertensive mice by decreasing superoxide.…”
Section: Antioxidative System In Ichmentioning
confidence: 99%